PENGARUH PERILAKU PEMIMPIN, KOMPENSASI, DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT. BANK MANDIRI CABANG DAAN MOGOT - Aziz, Abdul; Sitompul, Maruli; Purnawan, Yohan; Suranto, Suger (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
Abstract: The purpose of this study was to determine the effect of leader style, compensation, and job motivation toward employee job achievement at PT. Bank Mandiri Cabang Daan Mogot. The method uses multiple regression analysis and correlation. The results showed that partially and simultaneously the leader style, compensation, and job motivation of employee job achievement. The result of the correlation (R) of 0.890, indicating a correlation/relationship very strong between the leader style, compensation, and job motivation toward employee job achievement. The amount of the adjusted coefficient of determination (R2) is 0.781 or 78.1%, which means the independent variables can explain the change in the variable employee job achievement by 78.1% while the remaining 21.9% is explained by other factors outside of this research.